This action might not be possible to undo. Are you sure you want to continue?

17 Chapter 8

Fall 2004

8.4.1 Show that Legendre’s equation has regular singularities at x = −1, 1, and ∞. Legendre’s equation may be written as y − so that P (x) = − 2x 2x = , 2 1−x (x − 1)(x + 1) Q(x) = l(l + 1) l(l + 1) =− 2 1−x (x − 1)(x + 1) l(l + 1) 2x y + y=0 2 1−x 1 − x2

Written in this fashion, we see that both P (x) and Q(x) have simple poles at x = 1 and x = −1. This is suﬃcient to indicate that these two points are regular singular points. For the point at ∞, we make the substitution x = 1/z. As worked out in the text, we end up with P (z) = and Q(z) = Q(z −1 ) l(l + 1)/(1 − z −2 ) l(l + 1) = = 2 2 4 4 z z z (z − 1) 2z − P (z −1 ) 2z + 2z −1 /(1 − z −2 ) 2 2 2z = = + = 2 2 2 2 − 1) z z z z(z z −1

Examining the behavior of P and Q as z → 0, we see that P is regular, while Q has a double pole. Because of the double pole in Q, Legendre’s equation also has a regular singularity at x = ∞. 8.4.3 Show that the substitution x→ 1−x , 2 a = −l, b = l + 1, c=1

converts the hypergeometric equation into Legendre’s equation.

4·3 4! etc. In fact. .6 Develop series solutions for Hermite’s diﬀerential equation a) y − 2xy + 2αy = 0 Since x = 0 is a regular point. each coeﬃcient must vanish. y = n=0 nan xn−1 .5. we set a0 = 1 and ﬁnd a0 = 1. 2! a4 = 2(2 − α) 22 (−α)(2 − α) a2 = . one for n even and one for n odd. Since this series vanishes for all values of x. 8.1 Making the above substitution (along with dx → − 2 dx which implies y → (−2)y and y → (−2)2 y ) into the Hypergeometric equation. y = n=0 n(n − 1)an xn−2 Substituting this in to Hermite’s equation. we obtain two series. a2 = 2(−α) . given a0 and a1 as a starting point. we ﬁnd ∞ [n(n − 1)an xn−2 − 2nan xn + 2αan xn ] = 0 n=0 ∞ ⇒ n=0 [(n + 2)(n + 1)an+2 + 2(α − n)an ]xn = 0 To obtain the second line. we ﬁnd x(x − 1)y + [(1 + a + b)x − c]y + aby = 0 ⇒ 1−x 2 1−x 1−x − 1 (−2)2 y + (1 − l + (l + 1)) − 1 (−2)y 2 2 − l(l + 1)y = 0 ⇒ −(1 − x2 )y + 2xy − l(l + 1)y = 0 Changing an overall sign yields Legendre’s equation (1 − x2 )y − 2xy + l(l + 1)y = 0 This indicates that Legendre’s equation is in fact a special case of the more general Hypergeometric equation. For n even. we had made the substitution n → n + 2 in the ﬁrst term of the series so that we could collect identical powers of xn . we develop a simply Taylor series solution ∞ ∞ ∞ y= n=0 an xn . This yields the recursion relation 2(n − α) an+2 = an (1) (n + 2)(n + 1) which determines all higher an ’s.

and yodd terminates for α = 1. the series converges for all values of x. . yielding a ﬁnite ‘Hermite polynomial’. respectively. . Hence the solutions to Hermite’s equations are (generically) asymptotic to exp(2x2 ). all we need is to use the ratio test an xn (n + 2)(n + 1) n = lim = lim =∞ n→∞ an+2 xn+2 n→∞ 2(n − α)x2 n→∞ 2x2 lim (4) Since this is larger than 1. we would see that the n-th term in the Taylor series of the exponential is bn = (2x2 )n /n!. we did not have to solve the indicial equation. we would have found k = 0 or k = 1. . if we had chosen to do so. 3! a5 = 2(3 − α) 22 (1 − α)(3 − α) a3 = . which leads to a ratio bn−1 n = 2 bn 2x in direct correspondence with that of (4). 5. . for large index. Note that the ratio an /an+2 was directly obtained from the recursion relation (1).This gives the even solution yeven = 1 + 2(−α) x4 x6 x2 + 22 (−α)(2 − α) + 23 (−α)(2 − α)(4 − α) + · · · (2) 2! 4! 6! For n odd. This means the for α a non-negative integer either yeven or yodd (depending on α being even or odd) terminates. we set a1 = 1 and ﬁnd a1 = 1. b) Show that both series solutions are convergent for all x. Examination of the series solutions (2) and (3) indicates that yeven terminates for α = 0. 2. like the corresponding ratio in the expansion of exp(2x2 ). the ratio of successive coeﬃcients behaving. a3 = 2(1 − α) . and this result is valid for both yeven and yodd . . To test for convergence. c) Show that by appropriate choice of α the series solutions may be cut oﬀ and converted to ﬁnite polynomials. . yielding the even and odd solutions. This results in the odd solution yodd = x + 2(1 − α) x5 x7 x3 + 22 (1 − α)(3 − α) + 23 (1 − α)(3 − α)(5 − α) + · · · (3) 3! 5! 7! Note that. 3. and an ordinary point.. . 4. Furthermore. 5·4 5! etc. if we compared this with exp(2x2 ). However.

a+1 a(a + 1) a1 = . 2(c + 1) 2!c(c + 1) a+2 a(a + 1)(a + 2) a3 = a2 = 3(c + 2) 3!c(c + 1)(c + 2) a1 = a2 = a .5. c .11 Obtain two series solutions of the conﬂuent hypergeometric equation xy + (c − x)y − ay = 0 Test your solutions for convergence. we obtain ∞ [n(n − 1)an xn−1 + ncan xn−1 − nan xn − aan xn ] = 0 n=0 Making the substition n → n + 1 in the ﬁrst two terms and simplifying gives ∞ [(n + 1)(c + n)an+1 − (a + n)an ]xn = 0 n=0 Therefore we have a recursion relation of the form an+1 = a+n an (n + 1)(c + n) (5) Setting a0 = 1. we attempt an ordinary Taylor series solution ∞ ∞ ∞ y= n=0 an xn . q0 = 0 This shows that the indices at x = 0 are k1 = 0 and k2 = 1 − c. y = n=0 n(n − 1)an xn−2 Substituting this into the conﬂuent hypergeometric equation. y = n=0 nan xn−1 . We start with k1 = 0.8. We would like to develop a series solution around the regular singular point at x = 0. Since the index vanishes. the ﬁrst few terms in the series becomes a0 = 1. We ﬁrst observe that this equation has a regular singular point at x = 0 and an irregular one at x = ∞. Thus we start with the indicial equation y + and k(k − 1) + p0 k + q0 = 0 ⇒ k(k − 1) + ck = 0 ⇒ k(k + c − 1) = 0 c−x a y − y=0 x x ⇒ p0 = c.

unless c is a non-positive integer. we ﬁnd an xn (n + 1)(c + n) n = lim = lim =∞ n+1 n→∞ an+1 x n→∞ n→∞ x (a + n)x lim Therefore this series converges for all values of x. we seek a series solution of the form ∞ ∞ y = x1−c n=0 an xn . we obtain ∞ x 1−c n=0 [(n + 2 − c)(n + 1)an+1 − (n + 1 + a − c)an ]xn = 0 which yields the recursion relation an+1 = n+1+a−c an (n + 2 − c)(n + 1) . Turning next to k2 = 1 − c. We now test this series for convergence using the ratio test. Given the recursion relation (5).This indicates that a(a + 1) x2 a(a + 1)(a + 2) x3 a + + ··· y =1+ x+ c c(c + 1) 2! c(c + 1)(c + 2) 3! (a)n xn = (c)n n! n=0 where the notation (a)n is given by (a)n = a(a + 1)(a + 2) · · · (a + n − 2)(a + n − 1) = Γ(a + n) Γ(a) (7) ∞ (6) This is the ‘regular’ solution of the conﬂuent hypergeometric equation. in which case the denominators in (6) will eventually all blow up. we ﬁnd ∞ x 1−c n=0 [(n+1−c)(n−c)an xn−1 +c(n+1−c)an xn−1 −(n+1−c)an xn −aan xn ] = 0 Performing the shift n → n + 1 in the ﬁrst two terms and simplifying. ∞ y = x−c n=0 (n + 1 − c)an xn . y = x−1−c n=0 (n + 1 − c)(n − c)an xn Substituting this into the conﬂuent hypergeometric equation.

Supposing that a0 = 1. the ﬁrst few terms in this series are given by a0 = 1. we have only obtained one solution by the series method. For c = 1. for non-integer values of c. by the same ratio test argument as before. the interaction of two nucleons may be described by a mesonic potential Ae−ax V = x attractive for A negative. 8. 1+a−c 2+a−c (1 + a − c)(2 + a − c) . . 3. a2 = a1 = . where the denominators in (8) would eventually all blow up. we may write the series solution as ynew = x 1−c (1 + a − c)n xn (2 − c)n n! n=0 ∞ (8) This series is rather similar to the standard one (6). and we have found only one solution. the two solutions (6) and (8) form a complete linearly independent set. except when c = 2.5. [Why this works may be seen by making the substitutions directly into the conﬂuent hypergeometric equation itself. 4. it would be convenient to deﬁne E= 2mE .14 To a good approximation. ynew converges for all values of x. the solution of (6) may be converted into ynew by making the substitions a → a + 1 − c and c → 2 − c and multiplying y by the prefactor x1−c . h ¯2 A= 2mA h ¯2 . and the second solution would be of the ‘irregular’ form (which is not fun at all).] As a result. In fact. 2−c 2(3 − c) 2!(2 − c)(3 − c) 3+a−c (1 + a − c)(2 + a − c)(3 + a − c) a3 = a2 = 3(4 − c) 3!(2 − c)(3 − c)(4 − c) a1 = Following the notation of (7). For other integer values of c. both (6) and (8) are precisely the same. Develop a series solution of the resultant Schr¨dinger wave o equation h ¯ 2 d2 ψ + (E − V )ψ = 0 2m dx2 We begin by substituting the explicit potential in the Schr¨dinger equation o d2 ψ + dx2 2mE 2mAe−ax − h ¯2 h ¯ 2x ψ=0 As in the text. only one of (6) or (8) makes sense (and the other one blows up because of a bad denominator). . To summarize. . So in fact for all integer c.

Noting that P (x) = 0. Here we have to worry that e−ax is non-polynomial. we want to solve the second order equation ψ + E −A e−ax x ψ=0 (9) which has a regular singular point at x = 0 and an irregular one at x = ∞. k(k − 1) = 0. We now develop a series solution around x = 0.17 The modiﬁed Bessel function I0 (x) satisﬁes the diﬀerential equation x2 d2 d I (x) + x I0 (x) − x2 I0 (x) = 0 2 0 dx dx .5. Normalizing the ﬁrst term in the series to be x.In this case. we take y = x+a2 x2 +a3 x3 +· · · . q0 = 0 the indicial equation is trivial. Since we have k1 = 1 and k2 = 0. e−ax = 1 − ax + 2 a2 x2 − · · ·. we ﬁnd 0 = 2a2 + 6a3 x + · · · + (Ex − A(1 − ax + · · ·))(1 + a2 x + · · ·) = 2a2 + 6a3 x + · · · + (−A + (aA + E)x + · · ·)(1 + a2 x + · · ·) = 2a2 + 6a3 x + · · · + (−A) + (aA + E − a2 A)x + · · · = (2a2 − A) + (6a3 + aA + E − a2 A)x + · · · Setting the coeﬃcients to zero gives a2 = 1 A. y = 2a2 +6a3 x+· · · The series solution is the of the form 1 ψ = x + 2 Ax2 + 1 ( 1 A2 − E − aA)x3 + · · · 6 2 8. Substitution into (9) gives 2a2 + 6a3 x + · · · + (Ex − Ae−ax )(1 + a2 x + a3 x2 + · · ·) = 0 Since we have used a series for the wavefunction ψ(x). Keeping appropriate powers of x. 2 a3 = 1 (a2 A − E − aA) = 1 ( 1 A2 − E − aA) 6 6 2 y = 1+2a2 x+3a3 x2 +· · · . As a result. e−ax Q(x) = x ⇒ p0 = 0. we will not be able to obtain a simple recursion relation. we ought to also expand 1 the exponential as a series. We thus content ourselves with just working out a few terms in the series. we look for the k1 = 1 series (the larger index one always ‘works’).

even though it dropped out in the end. Here we are asked to develop an asymptotic expansion around x = ∞. in order to ﬁnd b1 and b2 . we write 1 3 5 7 ex I0 (x) ∼ √ (x− 2 + b1 x− 2 + b2 x− 2 + b3 x− 2 + · · ·) 2π The derivative d/dx acts either on the ex factor or the series in the parentheses. 8 b2 = 9 16 b1 = 9 128 so that the asymptotic series develops as ex 9 I0 (x) ∼ √ (1 + 1 x−1 + 128 x−2 + · · ·) 8 2πx Note that. we ﬁnd 3 1 1 3 ex 3 0 ∼ √ (x 2 + (b1 − 1)x 2 + (b2 − 3b1 + 4 )x− 2 + (b3 − 5b2 + 15 b1 )x− 2 + · · · 4 2π + x2 − x2 3 1 + (b1 − 1 )x− 2 2 − b2 x− 2 1 1 3 + (b2 − 2 b1 )x− 2 + · · · 3 3 − b1 x 2 1 − b3 x− 2 − · · ·) 1 3 ex 9 ∼ √ ((−2b1 + 1 )x− 2 + (−4b2 + 4 b1 )x− 2 + · · ·) 4 2π Setting the coeﬃcients to zero gives b1 = 1 . all we have to do is to take derivatives and insert the expressions into the diﬀerential equation. As a result. The resulting ﬁrst derivative is 1 3 5 7 ex 3 I0 (x) ∼ √ (x− 2 + (b1 − 1 )x− 2 + (b2 − 2 b1 )x− 2 + (b3 − 5 b2 )x− 2 + · · ·) 2 2 2π Taking one more derivative yields 1 3 5 7 ex 3 I0 (x) ∼ √ (x− 2 + (b1 − 1)x− 2 + (b2 − 3b1 + 4 )x− 2 + (b3 − 5b2 + 15 b1 )x− 2 + · · ·) 4 2π Substituting the above into the modiﬁed Bessel equation and collecting like powers of x. we are given the form of the series. Although this is an irregular one (witness the essential singularity ex ). we needed to keep track of the b3 coeﬃcient.4 the leading term in an asymptotic expansion is found to be ex I0 (x) ∼ √ 2πx Assume a series of the form ex I0 (x) ∼ √ (1 + b1 x−1 + b2 x−2 + · · ·) 2πx Determine the coeﬃcients b1 and b2 The (modiﬁed) Bessel equation has a regular singular point at x = 0 and an irregular one at x = ∞.4. . To make it easier to obtain the derivatives.From Exercise 7.

- Mathematical Methods For Physicists Webber/Arfken Selected Solutions ch. 8by Josh Brewer
- Mathematical Methods For Physicists Webber and Arfken Selected Solutions ch. 5by Josh Brewer
- Mathematical Methods For Physicists Webber and Arfken Ch. 3 Selected Solutionsby Josh Brewer
- Mathematical Methods For Physicists Webber and Arfken Selected Solutions Ch. 5by Josh Brewer

- Mathematical Methods For Physicists Webber/Arfken Selecet Solutions ch. 7by Josh Brewer
- Weber & Arfken Mathematical Methods For Physicists Ch. 5 selected Solutionsby Josh Brewer
- Weber & Arfken Mathematical Methods For Physicists Ch. 5 selected solutionsby Josh Brewer
- Mathematical Methods For Physicist Weber and Arfken Solutions Selected solutions ch. 10 & 14by Josh Brewer

- Mathematical Methods For Physicists 1.5.8 Solution Weber & Arfkenby Josh Brewer
- Webber And Arfen Mathematical methods for Physicists Seleceted Ch. 1 & 3 Solutionsby Josh Brewer
- Mathematical Method For Physicists Ch. 1 & 2 Selected solutions Webber and Arfkenby Josh Brewer
- Weber and Arfken Mathematical Methods for Physicist Ch. 9 solutionsby Josh Brewer

- Mathematical Methods For Physcists Webber/Arfken Selected solutions ch. 6 & 7by Josh Brewer
- Mathematical Methods for Physicists Weber & Arfken ch.15 & 17 selected solutionsby Josh Brewer
- Mathematical Methods For Physicists Solutions Ch. 2, Webber and Arfkenby Josh Brewer
- Mathematical Methods for Physicists Webber/Arfken Selected Solutions from ch. 6by Josh Brewer

- Mathematical Methods for Physicists Weber & Arfken 1.3.6 solutionby Josh Brewer
- Mathematical Methods for Physicists Weber & Arfken selected solutions ch. 2by Josh Brewer
- Mathematical Methods for Physicists Weber & Arfken selected solutions ch. 1by Josh Brewer
- Mathematical Methods for Physicists Weber & Arfken 1.3.3 solutionby Josh Brewer

- Mathematical Methods For Physicists Webber/Arfken Selected Solutions ch. 8
- Mathematical Methods For Physicists Webber and Arfken Selected Solutions ch. 5
- Mathematical Methods For Physicists Webber and Arfken Ch. 3 Selected Solutions
- Mathematical Methods For Physicists Webber and Arfken Selected Solutions Ch. 5
- Mathematical Methods For Physicists Webber/Arfken Selecet Solutions ch. 7
- Weber & Arfken Mathematical Methods For Physicists Ch. 5 selected Solutions
- Weber & Arfken Mathematical Methods For Physicists Ch. 5 selected solutions
- Mathematical Methods For Physicist Weber and Arfken Solutions Selected solutions ch. 10 & 14
- Mathematical Methods For Physicists 1.5.8 Solution Weber & Arfken
- Webber And Arfen Mathematical methods for Physicists Seleceted Ch. 1 & 3 Solutions
- Mathematical Method For Physicists Ch. 1 & 2 Selected solutions Webber and Arfken
- Weber and Arfken Mathematical Methods for Physicist Ch. 9 solutions
- Mathematical Methods For Physcists Webber/Arfken Selected solutions ch. 6 & 7
- Mathematical Methods for Physicists Weber & Arfken ch.15 & 17 selected solutions
- Mathematical Methods For Physicists Solutions Ch. 2, Webber and Arfken
- Mathematical Methods for Physicists Webber/Arfken Selected Solutions from ch. 6
- Mathematical Methods for Physicists Weber & Arfken 1.3.6 solution
- Mathematical Methods for Physicists Weber & Arfken selected solutions ch. 2
- Mathematical Methods for Physicists Weber & Arfken selected solutions ch. 1
- Mathematical Methods for Physicists Weber & Arfken 1.3.3 solution
- Mathematical Methods for Physicists Weber & Arfken Selected solutions ch. 1
- TI-83 Quadratic Program
- 19403003 Arfken Mathematical Methods CH 6 HW
- Mathematical Methods For Physicists Weber & Arfken selected Solutions ch. 1
- Math Methods for Physicist solutions Webber & Arfken
- Arfken Weber Math Selected Problem Solution
- Copy of Arfken Solution
- hw1S
- hw13a

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue reading from where you left off, or restart the preview.

scribd